Boosted UV Photodetection Performance in Chemically Etched Amorphous Ga2O3 Thin‐Film Transistors. Issue 8 (24th February 2020) - Han, Zuyin; Liang, Huili; Huo, Wenxing; Zhu, Xiaoshan; Du, Xiaolong; Mei, Zengxia
Abstract: A three‐terminal thin‐film transistor (TFT) architecture is essential for photodetectors to reach a good balance between high responsivity and fast response speed. Bottom‐gate amorphous Ga2 O3 (a‐Ga2 O3 ) TFTs are fabricated to boost their UV photodetection properties. During the device fabrication process, a simple chemical‐etching solution with the advantages of easy operation, low cost, and compatibility with traditional lithography process, is developed to selectively etch a‐Ga2 O3 films. The a‐Ga2 O3 channel etched device on Si manifests an effective suppression of the commonly observed gate leakage current. Meanwhile, a patterned a‐Ga2 O3 TFT on quartz shows an excellent n‐type TFT performance with an on/off ratio as high as ≈10 7 . It is further applied as a phototransistor, to diminish the persistent photoconductivity (PPC) effect while keeping a high responsivity ( R ) as well. Under the 254 nm UV illumination, the a‐Ga2 O3 phototransistor demonstrates a high light‐to‐dark ratio of 5 × 10 7, a high responsivity of 5.67 × 10 3 A W −1, and a high detectivity of 1.87 × 10 15 Jones. Remarkably, the PPC phenomenon in a‐Ga2 O3 UV phototransistors is effectively suppressed by applying a positive gate pulse, which greatly shortens the decay time to 5 ms and offers a‐Ga2 O3 possible inroads into imaging applications. Abstract : Amorphous Ga2 O3 thin‐film transistors with on/off ratio of ≈10 7 are fabricated using a highly selective etching method utlitizing tetramethyl ammonium hydroxide solution. These devices are further applied as phototransistors, demonstrating a high light‐to‐dark ratio of 5 × 10 7, a high responsivity of 5.67 × 10 3 A W −1 and an effective suppression of persistent photoconductivity with a decay time as low as 5 ms.